Efektivitas Model Pembelajaran React Terhadap Pemahaman Konsep Siswa Pembelajaran IPAS Materi Permasalahan Lingkungan Mengancam Kehidupan Kelas V SD Muhammadiyah Pangkalpinang - Oktaviani, Donna; Feni Kurnia; Erika Fitri Wardani (Universitas Muhammadiyah Bangka Belitung, 2025)
This research is motivated by a learning model that has not been implemented in learning, students' conceptual understanding in science learning has never been measured, and 59% of students' scores are still below the KKM. The purpose of this study was to determine whether there is an effectiveness of the REACT (Relating, Experiencing, Applying, Cooperating and Transferring) learning model on students' conceptual understanding of environmental problems that threaten the lives of grade V students of SD Muhammadiyah Pangkalpinang. This study uses a quantitative method with a Quasi Experimental Design research type. The sampling technique uses saturated sampling, which means that the entire population is used as a sample consisting of 32 students in the experimental class and 32 students in the control class in grade V of SD Muhammadiyah Pangkalpinang in the 2024/2025 academic year. The data collection technique uses a test of 10 essay questions. The data analysis technique uses a normality test, a homogeneity test and a hypothesis test. Based on the results of the analysis, it is known that the average value of the experimental class is higher than the control class (89.13 > 73.31). This is supported by the results of the hypothesis test using the independent sample t-test obtained a sig-2-tailed value of 0.000 < 0.05, so it can be concluded that there is an Effectiveness of the REACT Learning Model on Students' Conceptual Understanding of Science Learning on Environmental Problems Threatening Life in Class V of Muhammadiyah Elementary School Pangkal Pinang